Heat stress compromises epithelial integrity in the coral, Acropora hyacinthus - Traylor-Knowles, Nikki (PeerJ, 2019)
It is well understood that heat stress causes bleaching in corals. Much work has focused on the way heat stress disrupts corals’ symbiotic relationship with endosymbiotic algal dinoflagellate, Symbiodiniaceae, a process called bleaching. However, the damage to the coral tissue that occurs during the bleaching process and, importantly, the factors that contribute to subsequent recovery, are not well understood. I hypothesize that the host tissue damage created by heat stress initiates cascades of wound healing factors that maintain epithelial integrity. These factors may be found to contribute to the coral’s potential capacity to recover. In this study, I present evidence that heat stress causes damage to the coral host tissue and that collagen is present in the gastrodermis of heat-stressed corals. I found that, during the early stages of bleaching, an important transcription factor for wound healing, Grainyhead, is expressed throughout the gastrodermis, where the cellular and tissue rearrangements occur. Lastly, using phylogenetics, I found that cnidarian Grainyhead proteins evolved three distinct groups and that evolution of this protein family likely happened within each taxonomic group. These findings have important implications for our study of coral resiliency in the face of climate change.
Keywords: Coral bleaching; Heat stress; Grainyhead; Wound healing; Thermal stress